Building Self-Confidence Through Cooperative Learning STAD - Rahmawati Rahmawati; Eni Mintarsih; Ernie Setyawati; Romiati Ritonga (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2023)
The purpose of the study was to improve the ability of building self-confidence through cooperative learning STAD at SMPN 3 Pontianak to provide knowledge with what will be received during the learning process. The method with a quantitative descriptive research approach. Classroom Action Research (CAR) is a way of determining how to do it with cycles. I and II research activities, how to obtain this data is known as the data collection method, Data analysis with CAR is based on the results of research conducted during several meeting. It showed that in cycle 1, 26 students passed with a percentage of 81% and continued to cycle II with improvements in planning and implementation on target using the STAD cooperative learning model.